2021
DOI: 10.31703/gesr.2021(vi-iv).03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Teachers' Self Efficacy and Instructional Strategies on Students' Engagement at Secondary School Level

Abstract: The concept of self-efficacy was developed initially by Albert Bandura and has been defined as the personal belief that one can perform appropriately and effectively to attain specific goals related to any field. Self efficacy is a self-system that controls all our activities, including appropriate professional knowledge and skills.Teachers' self-efficacy is the belief that teachers have about their abilities and skills as educators. Both on an individualized and collective scale, teachers' efficacy is one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Hence, a high level of self-efficacy among pre-service teachers are capable of engaging students in learning activities, such as providing motivation to students, creating a comfortable learning atmosphere and encouraging students to think critically, and etc. As such, this is in accordance with Khalid & Akhter (2021) study found that higher self-efficacy affects teachers' ability to engage students in the classroom, which impacts students' learning.…”
Section: Resultssupporting
confidence: 90%
“…Hence, a high level of self-efficacy among pre-service teachers are capable of engaging students in learning activities, such as providing motivation to students, creating a comfortable learning atmosphere and encouraging students to think critically, and etc. As such, this is in accordance with Khalid & Akhter (2021) study found that higher self-efficacy affects teachers' ability to engage students in the classroom, which impacts students' learning.…”
Section: Resultssupporting
confidence: 90%
“…Studies on teachers' self-regulation are abundant and still posit strategic relevance for teacher professional development. An exploration of the effect of teachers' self-effi cacy and instructional practices on students' engagement at the secondary school level in Punjab was conducted by (Khalid & Akhter, 2021). Teachers with relatively higher self-effi cacy would have extraordinary ability to engage students with the material, pedagogical practice, and control of the classroom environment.…”
Section: Instructional Practicesmentioning
confidence: 99%